(3HGjhLjheJQi WGbI GdCTcGd GdMjhjI heONd Gdi JWHjbgG ai eLGd GdYeGQI (B/ s - (3eMeO CHhYQH eMeO YHO GddWjas; (3eOMJ OQI (B: s; (3gTGe SGeM (B: s ((3GdbGgQI (B: s (3eMeO CHhYQH eMeO YHO GddWja (B: s, 2020)
(3GdgfOSI GdeYeGQjI dgG CgejI YXej deG dgG ef CgejI aj JegjO GdMjGI dCfSGf Ydj hLI GdCQV agj CbQH GdYdhe hGdafhf hCcKQgG GMJcGckG HGdEfSGfjI aGdYeGQI JMhj GdMjGI GdGfSGfjI HeNJda UhQgG(B.(3dPG aGf GdGYeGd GdeYeGQjI jLH JdHj GdCMJjGLGJ GdhXjajI GdedGFeI dJCOjI GdfTGW GdeMOO dgG aj aQGZ efGSH dGjhGA ef HOGNdI hJhajQ GdQGMI GdeGOjI hGdhXjajI, hGdaGQZ GdeYeGQj jYJHQ COGI gGeI hCSGSjI ddhUhd HGdeSJNOe Gdj GdJCKjQ GdeWdhH(B.(3hdJMdjd GdaQGZ GdeYeGQj hechfGJg jecf GdQLhY Edj GdeSJhjGJ GdgfOSjI dgPG GdYedef (B)(3ehGO HfGA(B: (3fXe EfTGA (B:(3fSH aQGZjI (B:(3cJd(B: (3aJMGJ(B:....((3hOQGSI JCKjQ cd ef gPg GdeSJhjGJ Ydj JTcjd GdaQGZ GdeYeGQj hYdj YdGbJg HHGbj GdaQGZGJ aj GdcJdI GdhGMOI(B. (3aGdaQGZ GdeYeGQj jJMbb Yf WQjb JhajQehGO GdHfGAGdefGSHI hGSJNOGeg GdJTcjd GdeHfj aj cJd eJRfI hefSbI, gPG Gdj LGfH JOYje GdaQGZ HGdEfTGAGJ GdedGFI eGOjoG hJJeKd aj GdhXjaI, hQhMjkG JJeKd aj GdLeGd dEbGeI efXheI EfTGFjI eJRfI JJejR HGdcaGAI ajJTcjd GdaQGZGJ(B. (3jJfGhd gPG GdHMK GdMOjK Yf GdaQGZ GdeYeGQj hYdGbJI HGdWGbI hGdeTcdGJ GdJj JhGLg GdeHfj, hWGbI GdCTcGd GdMjhjI (B((3GdHjhLjheJQj(B) (3hJWHjbGJgG aj eLGd GdYeGQIs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdgfOSI (B- (3bSe GdgfOSI GdeYeGQjI s
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdeHGfi GdeQjVI s; (3HGjhLjheJQj s; (3QGOjSJjG s